Al-Imām al-Bukhārī wa Raʻyuh fī Bayʼ al-Ḥayawān bi al-Ḥayawān wa Athār Ikhtilāf al-ʼUlamāʻ fī hā - Desmadi Syahruddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2006)
Many people thought that Imam Bukhari is well-known by his book Shahih Bukhari or a master of Hadits only. He also is master of Islamic Jurisprudence (Fikih). This paper describe his opinion of trading rules of animal by animal, and opinion of other mazhab scholars (Ulama) about that.